Exercise Dependence and Anxiety in Cross-Trainers, Bodybuilders and Gym Exercisers During COVID19. Issue 4 (August 2022) - Salvador, Rogério; Frontini, Roberta; Ramos, Catarina; Lopes, Pedro; Oliveira, Janete; Maia, Joana; Monteiro, Diogo
The World Health Organization declared the COVID-19 pandemic an international public health emergency in January 2020, and, soon thereafter, a worldwide adoption of quarantine and physical isolation measures restricted regular practitioners of indoor group physical exercise from many of their usual practices. Some, with exercise dependence (ED), may have experienced exercise withdrawal symptoms that triggered unhealthy anxiety levels. In February 2021, during Portugal's second COVID-19 lockdown, we characterized and compared ED and anxiety levels among different groups of indoor exercise practitioners (cross trainers [CG], bodybuilders [BG] and gym practitioners [GG]). In this cross-sectional study, we recruited 234 adult participants through the internet. To assess participants' ED and anxiety levels, we used Portuguese versions of the ED Scale-21 (EDS-21) and the State-Trait Anxiety Inventory (STAI-State; STAI-Trait). ED symptoms were evident in all participant subgroups, and we found no gender differences in ED. Anxiety was higher among women than men in CG and GG groups, and there were significant differences in ED between groups such that BG practitioners showed higher ED than GG and CG practitioners (small effect size). Bodybuilders reported most ED behavior, followed by CG and regular gym exercisers, but on some criteria BG and CG groups had similar ED levels. Our results are in line with prior ED prevalence reports conducted before COVID-19 restrictions among regular GG, but these are the first data to report a higher ED prevalence among BG and CG, relative to GG.